2014
DOI: 10.1186/1687-1499-2014-223
|View full text |Cite
|
Sign up to set email alerts
|

A survey on communication technologies and requirements for internet of electric vehicles

Abstract: Electric vehicles (EVs) are becoming a more attractive transportation option, as they offer great cost savings, decrease foreign oil dependency, and reduce carbon emissions. However, varying temporal and spatial demand patterns of EVs threatens power grid operations and its physical components. Thus, the ability of the power grid to handle the potential extra load has become a major factor in the mainstream success. In order for this integration to occur seamlessly, the power grid and the consumers need to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 95 publications
0
31
0
Order By: Relevance
“…With standardization and better information regarding the charging facilities and vehicle interface, the distribution network can be based on their own situation to control BEV charging times, reducing charging facilities equipment investment. Bayram and Papapanagiotou [67] showed that the grid was becoming congested due to the introduction of BEV charging points, particularly the use of household charging points. Management and control of charging requirements should be consistent with the available resources.…”
Section: Discussionmentioning
confidence: 99%
“…With standardization and better information regarding the charging facilities and vehicle interface, the distribution network can be based on their own situation to control BEV charging times, reducing charging facilities equipment investment. Bayram and Papapanagiotou [67] showed that the grid was becoming congested due to the introduction of BEV charging points, particularly the use of household charging points. Management and control of charging requirements should be consistent with the available resources.…”
Section: Discussionmentioning
confidence: 99%
“…The key to such growth is 'connectivity' [17]. Additionally, Gartner Research has forecast that the number of digital devices connected within all worldwide networks will amount to over 26 million units by 2020, rising to 100 billion during the next few years.…”
Section: Trend Of Communication In Smart Home Architecturementioning
confidence: 99%
“…Networked social network has changed the organizational structure and operation strategy of traditional business models [5][6][7][8][9]. Information networking, especially the wireless communication network, has changed the information flow and decision-making mechanism of traditional business models [10][11][12]. In addition, in view of the growing value of the network [13,14], enterprises have seen the way to promote the development of the enterprise by optimizing the value network.…”
Section: Introductionmentioning
confidence: 99%